The continuous spontaneous localization layering effect from a lattice perspective. (5th February 2021) - Adler, Stephen L; Bassi, Angelo; Carlesso, Matteo
Abstract: For a solid lattice, we rederive the continuous spontaneous localization (CSL) noise total energy gain of a test mass starting from a Lindblad formulation, and from a similar starting point rederive the geometry factor governing center of mass energy gain. We then suggest that the geometry factor can be used as a way to distinguish between low temperature cantilever motion saturation arising from CSL noise, and saturation arising from thermal leakage.